Optimization of Injection Pressure and Time of Injection Molding for Eye Drop Heads - Ichlasul Insani; Andoko Andoko; Yanuar Rohmat Aji Pradana (TRANSMISI, 2023)
Injection molding is a plastic production process by injecting liquid plastic into a mold. One of the injection molding products is an eye drop head. Eye drops in its production experienced rejects reaching 37.5% due to defects. The purpose of this optimization is to obtain the optimum setting of injection pressure and time of injection molding machine using RSM. The method to achieve the goal through finite element approach with pre-processing includes design and setting boundary conditions for injection pressure (10.5, 11, and 11.5 MPa) and injection time (1.9, 2.0, and 2.1 seconds). Post processing displays the results of product mass, defects, and quality prediction which are further optimized using RSM to obtain optimum values. The simulation results show that higher injection pressure and lower injection time have given satisfactory results for all three parameters (product mass, defects, and quality prediction) observed. Based on the optimization results, the optimal injection molding settings were obtained at an injection pressure of 11.5 MPa and injection time of 1.9 seconds which resulted in a product mass of 0.429 g, weld line defect of 0.1384, and quality prediction of 80.9%.